VERONIKA`S PERSONALITY DETERMINANT AND EGO-STATE IN VERONIKA DECIDE TO DIE IN PAULO COELHO - Tawali Tawali (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2016)
This research is aimed to revel the personality determinant and Veronika`s ego-state. The theory that applied in this research is personality determinant by Elizabeth Hurlock and transactional analysis proposed by Eric Berne. The method used in this research is qualitative descriptive method. The condition that Veronika experiences is that her mother in determining her future pressures Veronika`s life. Everything that she wants to do, it must be controlled by her mother. Finally, she feels tired living with that condition therefore she prefers to end up her life through suicide. Unlikely, she is failure in doing it. It is found out aspiration and achievement, education, social, emotion, family, sex, physical, and intellectual factor determinant her personality. However, her personality is dominant by family factor. Her view in relationship toward a life and death are she feels happy living when she was to child. However, she feels empty when she is adult women and has everything. She gets bored with her routine activity such as go for working in the morning and gets back in the afternoon. She has not any purpose of life anymore. Since living the mental hospital, her life rise back. She understands the meaning of life through motivation from her friends and love from young man. There are three aspects of her ego-state within her such as parents, adult, and child aspects. However, the adult ego state determinates from them all.